2015
DOI: 10.3747/pdi.2014.00347
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned Start on Peritoneal Dialysis Right after Pd Catheter Implantation for Older People with End-Stage Renal Disease

Abstract: Unplanned start on dialysis remains a major problem for the dialysis community worldwide. Late-referred patients with end-stage renal disease (ESRD) and urgent need for dialysis are overrepresented among older people. These patients are particularly likely to be started on in-center hemodialysis (HD), with a temporary vascular access known to be associated with excess mortality and increased risks of potentially lethal complications such as bacteremia and central venous thrombosis or stenosis.The present paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 10 publications
3
33
0
Order By: Relevance
“…This clinical scenario is somewhat reminescent of the resurgent momentum of urgent-start PD program, in which patients starting PD within 2 weeks after placement of the PD catheter exhibited outcomes comparable to the traditionally planned counterpart [ 5 , 7 , 8 ]. It is advocated that urgent-start PD be a sound treatment option for late-referred CKD patients who do not have a mature vascular access at the time of dialysis initiation [ 6 , 10 , 21 ]. Similarly, data accrued from this study suggest that post-initiation PD can be a relatively safe long-term dialysis treatment for late-referred CKD patients, given the poor outcome of the concurrent emergent-start HD-CVC patients who commenced long-term dialysis with a tunneled cuffed CVC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This clinical scenario is somewhat reminescent of the resurgent momentum of urgent-start PD program, in which patients starting PD within 2 weeks after placement of the PD catheter exhibited outcomes comparable to the traditionally planned counterpart [ 5 , 7 , 8 ]. It is advocated that urgent-start PD be a sound treatment option for late-referred CKD patients who do not have a mature vascular access at the time of dialysis initiation [ 6 , 10 , 21 ]. Similarly, data accrued from this study suggest that post-initiation PD can be a relatively safe long-term dialysis treatment for late-referred CKD patients, given the poor outcome of the concurrent emergent-start HD-CVC patients who commenced long-term dialysis with a tunneled cuffed CVC.…”
Section: Discussionmentioning
confidence: 99%
“…Despite wide-spread promotion of planned-start dialysis therapy for patients with advanced chronic kidney disease (CKD), there remain patients who are referred ultra-late to the nephrologists, [ 4 , 10 ] and acute dialysis has to be initiated via a temporary hemodialysis (HD) catheter due to life-threatening uremic emergency [ 11 , 12 ]. After stabilization of vital conditions, most such patients tend to choose HD out of convenience as the long-term dialysis modality, [ 10 , 13 ] although some may select post-initiation PD, i.e., emergent-start PD, as the treatment option. Compared to the above-mentioned urgent-start PD which is considered a safe and effective option of dialysis initiation, data are still limited regarding the impact of emergent-start PD in new-onset patients with ESRD [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ivarsen and Povlsen [1], Povlsen et al [8] and Liu et al [16] showed that total mechanical complications occurred significantly more in urgent-start than conventional start PD [1,8,16]. They noted that there was an increased need for surgical replacement of PD catheter in the urgent group.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the rate of technique survival was 86% at 180 days. Povlsen et al [8] and Ivarsen and Povlsen [1] looked at technique survival at 3 months in their urgent start PD group and it was 86.7 vs. 90%, respectively [8,1]. Song et al [17] showed that catheter survival at 1 year was about 85%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation